AN ANALYSIS OF SEMANTIC MEANING IN THE TOURING INSTRUCTIONS OF AUTOMOTIVE CLUB “MERCEDES BENZ W211” - NURFITHRI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
This research focusses on analyzing semantic meaning in The Touring Instructions Of Automotive Club “Mercedes Benz W211”. The semantic meaning includes lexical and contextual meaning. By listening to the touring instruction, we can get knowledge about appreciation literature and the background of the touring instruction. Therefore, the researchers were interested in analyzing the kinds of lexical meaning and contextual meaning used in touring instruction. The researchers dedicated to give the title of this research “An Analysis Of Semantic Meaning In The Touring Instructions Of Automotive Club “Mercedes Benz W211””. The problem of this research are: (1) what are the lexical meaning in the touring instruction of Automative club Mercedes Benz W211? (2) what are the contextual meaning in the touring instruction of Automative club Mercedes Benz W211? The researchers found 16 data from touring instruction that have both meaning, lexical and contextual meaning. This research uses a descriptive method by analyzing the research object of Elevation Worship Song Lyrics. To obtain the data, the researchers collected the data from the touring instruction that are said by using Handy Talky (HT) . The result of this research are as follows: the lexical and the contextual meanings are used in the touring instruction of MBW211 Club. There are 16 data showing that their instruction has several words containing contextual meaning. For people in first time joining the touring activity, they may be confused and afraid of the meaning and message from the commander. Because contextual meaning is similar to ‘something means something else’. This is the concept of literature, art of language